Turnover intention of employees in Malaysia’s service industry: the role of personal employee dimensions and retention strategies / Mutiiah Mohamad - Mohamad, Mutiiah (2023)
Turnover is a significant theme for study since it has created significant issues in the context of working environment. The scenario of employees resigning from a company only after a few months of working in order to seek for greener pasture happened in most companies in Malaysia. Therefore, the issue of employees’ turnover intention must be dealt with an appropriate manner. This research was conducted in Malaysia’s service industry with the service employees involved as the unit of analysis. The purpose of this study is to investigate the factors of personal employee dimensions (emotional exhaustion, role ambiguity, role conflict, person-job fit, and person-organization fit) as determinants of employee turnover intention. Moreover, the present study is also intended to examine the moderating effect of retention strategies (rewards and benefits, working environment and training) on the relationship between the independent variables and the dependent variable. The study used the purposive sampling method to select the respondents. The questionnaire was developed by referring to the published work and distributed via online survey platform to the selected respondents. Respondents of this research consist of 679 individuals who are employees of the service industry. The findings indicate that there is a significant relationship between personal employee dimensions and turnover intention except for role conflict. Furthermore, the findings confirm the partial moderating effect of the retention strategies (rewards and benefits and working environment) on the relationship between personal employee dimensions and employee turnover intention. Nevertheless, none of personal employee dimensions was found to have significant interaction with training to affect turnover intention. The findings of this study contribute to the management literature by adding new empirical evidence on the relationship among the three constructs: personal employee dimensions, retention strategies and turnover intention. In terms of managerial implications, the findings help Malaysia’s service industry to reduce turnover intention among employees in the company particularly with regard to personal employee dimensions.